kifli PENERAPAN METODE RESITASI DI MASA NEW NORMAL PADA MATA PELAJARAN IPS KELAS V DI SDN INPRES PAKOWA KABUPATEN BANGGAI - kifli bonenehu; karmawati karmawati; Rahmawaty Rahmawaty (IBTIDAI'Y DATOKARAMA: JURNAL PENDIDIKAN DASAR, 2021)
This thesis discusses "Application of the Recitation Method in the New Normal Period in Social Studies Subject Class V SDN Inpres Pakowa Banggai Regency. The main research problems are the application process of the recitation method in social studies subjects for a fifth-grade student at SDN Inpres Pakowa Banggai Regency during the new-normal period. Together with factors that hinder the implementation recitation method in social studies subjects class V SDN Inpres Pakowa Banggai Regency in the "new normal" period. The purpose of this study was to determine the application of the recitation method to social studies subjects for class V at SDN Inpres Pakowa, Banggai Regency during the new-normal period and to find out the inhibiting factors for implementing the recitation method in the new-normal period in social studies subjects for class V at SDN Inpres Pakowa, Banggai Regency. This type of research uses qualitative research by describing information data based on facts (facts) obtained in the field. Data collection techniques in this study used observation, interviews, and documentation techniques to describe the learning process at SDN Inpres Pakowa, Banggai Regency during the new-normal period, especially in class V at SDN Inpres Pakowa. The research result shows that SDN Inpres Pakowa applies one of the learning methods to assist the continuity of learning, namely the recitation method or what is known as the assignment method. The learning process was implemented offline at SDN Inpres Pakowa during the new-normal period. The application of the recitation method was carried out by dividing two groups into one class consisting of 14 people divided into 7th people per group. There are inhibiting factors in the new-normal period, namely learning inhibiting factors, lack of learning resources, and weaknesses in applying the recitation method.